Dimensions of Healthcare Services in Bangladesh: A Systematic Literature Review - Md. Ruhul Amin (Universitas Airlangga, 2026)
Introduction: Bangladesh has achieved substantial gains in the enhancement of population health outcomes; however, unresolved issues of inequality in healthcare access, equity, and quality hamper the success of the health system. Current literature is usually disjointed in its findings and fails to provide a national focus on policy and change. This systematic review fills this gap by summarizing the existing evidence to assess trends in healthcare access, factors that contribute to inequity, disparities in service quality, and major structural and policy issues. Method: This review followed the PRISMA guidelines to ensure methodological rigor and transparency. Secondary data were collected from peer-reviewed articles and grey literature published between 2010 and 2024. Electronic databases, including PubMed, Google Scholar, and ScienceDirect, were searched alongside reports from reputable institutions, such as the Ministry of Health and Family Welfare and the World Health Organization. Result: After screening and quality assessment, 35 studies that met the inclusion criteria were included in the study. According to the findings, there is limited healthcare access in rural and underserved regions because of a shortage of workforce and gaps in infrastructure. Equity analysis shows huge differences in terms of income, gender, and location. Quality measurement reflects the inconsistent standards of services, and patient satisfaction depends mainly on the tangibility of services, responsiveness, and facility preparedness. Conclusion: The healthcare system in Bangladesh continues to struggle with structural barriers that influence accessibility and quality consistency. Rural development, equal distribution of resources, empowering the workforce, and policies of uniform quality enhancement are fundamental to providing equitable and accessible high-quality healthcare in all regions of the country.